Analisis Kebutuhan Sarana dan Prasarana Kawasan Kumuh di Kabupaten Sambas - Deny Syahrani; Etty Rabihati; Rasiwan Rasiwan (Vokasi, 2021)
As a result of the COVID-19 Pandemic Outbreak, proper living for slum dwellers has become increasingly difficult, the income level of the population has decreased so that areas where slum areas were not identified at first may increase the spread of their territory. According to the Decree of the Regent of Sambas Number 872 / BAPPEDA of 2014 concerning the Determination of the Location of Housing and Slum Settlements in Sambas Regency, the slum settlement area covering an area of ​​75.77 ha is spread over 3 sub-districts covering 4 villages. Namely Pendawan Village, Tanjung Bugis Village in Sambas District, Penjajab Village, Penjajab District and Sekura Village, Sekura District. Of the 4 villages that occupy the largest area for slum areas is Tanjung Bugis Village with an area of ​​23.05 ha (30.42%). This study aims to identify the factors that cause slum areas in Sambas Regency, identify facilities and infrastructure, especially environmental roads, garbage, wastewater and housing, analyze the needs for facilities and infrastructure from the data obtained in the form of roads, to, clean water and housing. This research was conducted deductively, so that the researchers departed from theory to go into the field in conducting data searches which were then expected to analyze the facilities and infrastructure needs of the slum area in Sambas City. .From the results of this study, it is found that the factors that cause slum are insufficient income of Rp. 500,000 - Rp. 1,000,000.00, the last education is very low elementary school (elementary school) and the number of families between 3-5 people. Meanwhile, from the analysis of the need for facilities and infrastructure, appropriate technology is needed for community water sources that still use public taps, environmental roads use concrete rebates but many are still damaged, drainage channels are not there if the water is not smooth or jammed while the trash can is not owned, especially TPS (Temporary Disposal Site) for garbage.